Microbial scoping of plant-based meat analogues in Philippine retail - Bombase, Adriana Roni C.
Plant-based meat analogues (PBMAs) represent an emerging food category with a crucial paucity in microbial quality and safety information in international and local markets. To address this, the present work evaluated the microbial loads of PBMAs in the Philippines using indicators for bacteria (APC), fungi (YMC), coliforms (TCC), psychrotrophs (PPC) and Staphylococcus aureus (SAC). Products were grouped by protein (Non-Legume, Legume, Soy) and form (Ground, Whole) and compared based on indicators. Microbial loads ranged from <1.00 to 5.23 log cfu g-1 with considerable variation between tests and samples. Ground Non-Legume samples had the highest counts for APC (3.22 log cfu g-1), YMC (3.21 log₁₀), PPC (4.20 log₁₀), and SAC (5.23 log₁₀). Conversely, Soy samples had lowest variance and mean counts for all indicators except PPC. Legume samples exhibited intermediate results ranging from <1.00–4.16 log cfu g-1 and represented the only samples with detectable TCC (1.77 log cfu g-1 in Ground Legume). PPC and SAC were generally higher for Ground samples compared to Whole counterparts. These results illustrate important factors contributing to the microbial complexity of PBMAs and highlight the need for further research to inform industry best practices and development of suitable regulations.